Academic mobility and international academics : challenges and opportunities - Singh, Jasvir Kaur Nachatar (Surviving and thriving in academia, 2022)
Despite growing numbers of international academics globally, there is a dearth of works exploring success stories, and the barriers and opportunities of being an international academic. Academic Mobility and International Academics offers personal experiences and guidance from a truly international suite of scholars exploring their academic journeys and addressing intersectional topics on academic mobility including perspectives from early career researchers, university leaders, mentors, LGBTIQ scholars, and more. Throughout this timely collection, chapter authors offer insight into overall academic employment experiences, including their motivations and challenges in steering their academic career. They offer guidance on how international academics can harness their career aspirations, across both leadership and non-leadership positions and how internationality in academic careers is evolving in these current times. Essential reading for any scholar or postgraduate student looking to work outside of their home nation, this hopeful and insightful text will provide guidance, inspiration, and real-life examples of how to survive and thrive as an international scholar.